2022
DOI: 10.3389/fgene.2021.818697
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alternative Polyadenylation in Cyanidioschyzon merolae Through Long-Read Sequencing of mRNA

Abstract: Alternative polyadenylation (APA) is widespread among metazoans and has been shown to have important impacts on mRNA stability and protein expression. Beyond a handful of well-studied organisms, however, its existence and consequences have not been well investigated. We therefore turned to the deep-branching red alga, Cyanidioschyzon merolae, to study the biology of polyadenylation in an organism highly diverged from humans and yeast. C. merolae is an acidothermophilic alga that lives in volcanic hot springs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 60 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, some of these absent proteins and domains, such as the Prp18–Slu7 heterodimer, or the Toggle loop of the Prp8 RNase H domain, are proposed to act as throttles that normally allow the spliceosome to shift between two states: slow and accurate versus fast and inaccurate. The absence of such domains is consistent with the low fraction of spliced transcripts observed in Cm ( Stark et al 2015 ; Schärfen et al 2022 ), although we have not observed evidence of inaccuracy: while some cryptic splice site use is detected by Illumina and PacBio sequencing, there do not appear to be more of these in Cm than in other organisms ( Schärfen et al 2022 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Interestingly, some of these absent proteins and domains, such as the Prp18–Slu7 heterodimer, or the Toggle loop of the Prp8 RNase H domain, are proposed to act as throttles that normally allow the spliceosome to shift between two states: slow and accurate versus fast and inaccurate. The absence of such domains is consistent with the low fraction of spliced transcripts observed in Cm ( Stark et al 2015 ; Schärfen et al 2022 ), although we have not observed evidence of inaccuracy: while some cryptic splice site use is detected by Illumina and PacBio sequencing, there do not appear to be more of these in Cm than in other organisms ( Schärfen et al 2022 ).…”
Section: Discussionsupporting
confidence: 85%
“…We suggest Cm splicing—and by analogy that of other organisms with reduced spliceosomes—to be inefficient, inaccurate, and post-transcriptional. The inefficiency of Cm splicing contrasts strongly with splicing efficiency in other organisms including yeast ( Stark et al 2015 ; Schärfen et al 2022 ). Furthermore, Cm lacks the DEAD-box RNA helicase Prp28, which is not only associated with release of U1 snRNP, but also with proofreading the 5′SS and splicing fidelity ( Price et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the analysis of splicing efficiency and APA, we followed the methodology described in Schärfen et al . (2022) .…”
Section: Methodsmentioning
confidence: 99%